2020
DOI: 10.1007/s00520-019-05259-1
|View full text |Cite
|
Sign up to set email alerts
|

Determining the prevalence and severity of cancer cachexia in advanced non-small cell lung cancer and its relationship with chemotherapy outcomes

Abstract: Purpose Cancer cachexia (CC) is a syndrome characterised by an ongoing loss of skeletal muscle mass associated with reduced tolerance to treatment. This study explored the prevalence and severity of CC in advanced non-small cell lung cancer (NSCLC) patients and determined its relationship with chemotherapy outcomes. Methods CC was classified into a four-stage model: no cachexia, pre-cachexia (PC), cachexia and refractory cachexia (RC) with categorisation determined from biochemical and body composition and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Chemotherapy is widely used in the treatment of cancer (Frei 3rd., 1985), but many chemotherapeutic drugs can induce cachexia while suppressing tumour growth. Cancer patients will experience weight loss, body mass index loss, and sarcopenia after chemotherapy (da Rocha et al, 2019; Nattenmuller et al, 2017; White, Weekes, Grant, Baldwin, & Ahmed, 2020). Muscle loss in cancer patients during chemotherapy is associated with poor chemotherapy efficacy and poor prognosis (Daly et al, 2018; Griffin et al, 2019; Sasaki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is widely used in the treatment of cancer (Frei 3rd., 1985), but many chemotherapeutic drugs can induce cachexia while suppressing tumour growth. Cancer patients will experience weight loss, body mass index loss, and sarcopenia after chemotherapy (da Rocha et al, 2019; Nattenmuller et al, 2017; White, Weekes, Grant, Baldwin, & Ahmed, 2020). Muscle loss in cancer patients during chemotherapy is associated with poor chemotherapy efficacy and poor prognosis (Daly et al, 2018; Griffin et al, 2019; Sasaki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Systemic inflammation requires further exploration to determine whether it should form part of the CC staging. 32 In the study population, only 9% were not on active antitumor therapy; most were being treated with palliative intent and/or have metastatic disease. This likely impacted the prevalence of CC identified.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even though recruitment during the NOURISH trial was focused at the earliest point in the clinical pathway, rather than only after symptoms of cachexia were noted, this trial concluded these issues still persisted suggesting most if not all patients who took part were not precachectic. It is interesting to note that, given the high proportion of NOURISH trial patients with NSCLC with metastatic disease, a very recent study suggests the majority of patients with advanced NSCLC present with some degree of cachexia [32].…”
Section: Discussionmentioning
confidence: 99%